Highly efficient AgNO3‐catalyzed approach to 2‐(benzo[d]azol‐2‐yl)phenols from salicylaldehydes with 2‐aminothiophenol, 2‐aminophenol and benzene‐1, 2‐diamine. (8th February 2018) - He, Xinwei; Wu, Yuhao; Jin, Wenjing; Wang, Xiaoshun; Wu, Cong; Shang, Yongjia
Abstract : A new, convenient and efficient AgNO3 ‐catalyzed strategy for the preparation of 2‐(benzo[ d ]azol‐2‐yl)phenol derivatives in good to excellent yields (63–98%) is described. The reaction proceeds via condensation/intramolecular nucleophilic addition/oxidation process between substituted salicylaldehydes and 2‐aminothiophenol, 2‐aminophenol or benzene‐1, 2‐diamine under mild reaction conditions. Notably, this reaction utilizes cheap AgNO3 as a readily available and low‐cost benign oxidant at low catalyst loadings with excellent functional group tolerance. Abstract : A high efficient strategy for the preparation of 2‐(benzo[ d ]azol‐2‐yl)phenol derivatives in good to excellent yields was described. This reaction utilized cheap AgNO3 as a readily available and low‐cost benign oxidant at low‐catalyst loadings with excellent functional group tolerance.